Role of mirabegron in the management of overactive bladder: a knowledge, attitude, and practice survey among Indian healthcare professionals - Agrawal, Madhu Sudan; Pandey, Sanjay; Kumar, Prem; Sahu, Vikram; Patil, Dinesh (International Journal of Research in Medical Sciences, 2024)
Background: Overactive bladder (OAB) is identified by urinary urgency, with or without urgency urinary incontinence, typically accompanied by increased daytime urinary frequency and nocturia, in the absence of proven infection or other evident pathology. Methods: A cross-sectional, observational, questionnaire-based knowledge, attitude, and practice (KAP) survey was conducted across India from January 2022 to July 2023 to understand OAB therapy through 14 multiple–choice questions containing questionnaire shared with 1, 029 healthcare professionals (HCPs), including urologists, surgeons, nephrologists, and consulting physicians. Results: The HCPs see 10-20% of patients daily in clinical practice, wherein 5-10% are females. Patients usually consult general practitioners first and then other specialists. Although anticholinergics are commonly used in the management of OAB, HCPs reported that side effects (57%) and the high cost of therapy (43%) were mainly responsible for discontinuing anticholinergics. Mirabegron was preferred by 67% of HCPs in the treatment of these patients. Mirabegron is also preferred as a first-line treatment by all HCPs in this survey. It is prescribed for 6-12 months, has a response rate of >75% in clinical practice, and offers a more favourable side-effect profile compared to anticholinergics. In cases where patients do not respond to anticholinergics or experience treatment failure, a combination therapy of mirabegron and solifenacin is preferred. Conclusions: The survey highlights the use of mirabegron as a first-line treatment for OAB, its better side-effect profile, and its role in combination therapy with solifenacin for patients unresponsive to anticholinergics, ultimately improving the quality of life of patients.